A simple and rapid method to assay SARS-CoV-2 RNA based on a primer exchange reaction. Issue 28 (18th March 2022) - Li, Dayong; Duan, Chengjie; Cheng, Wenting; gong, Youjing; Yao, Yanheng; Wang, Xiaoping; Wang, Zhongyun; Xiang, Yang
Abstract : Integrating the PER cascade and CRISPR/cas12 system for the rapid detection of SARS-CoV-2 RNA. Abstract : A simple method is proposed in this work for the detection of SARS-CoV-2 RNA based on a primer exchange reaction (PER). By ingeniously integrating the PER cascade and CRISPR/cas12a system, this method can achieve convenient detection of the target RNA in 40 min and distinguish a single-base mutation from the target sequence, demonstrating its superior analytical performance.